Pemanfaatan Alat Peraga Perkalian Berbasis Metode Montessori Pada Pembelajaran Matematika Perkalian Kelas II Di MI AR ROFI - Sas Hariana Putri; Tiurlina; Fitri Alfarisa (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
This research is based on the results of research by using multiplication teaching aids based on the Montessori method in learning mathematics in class II MI Ar-Rofi. Because mathematics is abstract, it is easy for students to understand if the delivery is clear with the help of props. This can be seen in the teacher's learning in delivering using the lecture method and giving questions followed by copying the questions into notebooks and seen in the learning outcomes of many students who are less than the KKM (78). The problem is suitable with the aid of teaching aids that make it easier for students to understand it. The research used was classroom action research which was carried out in 2 cycles, starting with planning, implementing, viewing, and reviewing. Class II students of MI Ar-Rofi, totaling 25 students, became the subject. Teacher observations, student activity observations, motivational questionnaire sheets, and student learning outcomes tests are data collection techniques. The acquisition of motivation and the acquisition of student learning increases each cycle. Obtaining student response questionnaires on the use of multiplication teaching aids in the pre-cycle obtained an average of 21.92, the percentage of 55% in the first cycle rose to 25.76, the percentage of 64% in the second cycle, obtaining an average of 28.52 with a percentage of 71% in the